Embryonic development after 48 hours in vitro fertilization with mice epididymal sperms activated in vitro by male Fertility Blend medium - Dr. Sara Radi Farhan; Dr. Shahad Jamal Mohamed; Nisreen salih abd (Genius Journals, 2022)
The new nutritional supplement Male Fertility Blend (MFB) has a diversity of ingredients, counting Dong qui excerpt, which may improve sperm motility, superiority, and quantity. The new nutritional supplement Male Fertility Blend(MFB) has a diversity of elements, including Dong qui excerpt, which may improve sperm motility, quality, and quantity
Keywords: Primary development; Sperm; Conception; grading